النظام القانوني للجباية البترولية في الجزائر - مخنان, عقبة; بامون, لقمان (Revue jurisprudence, 2019)
This study aims to present the legal system of petroleum taxes In Algeria, since the first commercial discovery of oil in 1953, the effective date of desert petroleum law down to the current period known as reforms period after the issuance of law 05 - 07 amended and completed by order 10 - 06. Each time, changes were applied relative to prevailing conditions which committed the Algerian legislator to adapt with each situation using total and partial amendments.